Photonic devices fabricated from (111)‐oriented single crystal diamond. Issue 6 (6th February 2020) - Regan, Blake; Kim, Sejeong; Ly, Anh T. H.; Trycz, Aleksandra; Bray, Kerem; Ganesan, Kumaravelu; Toth, Milos; Aharonovich, Igor
Abstract: Diamond is a material of choice in the pursuit of integrated quantum photonic technologies. So far, the majority of photonic devices fabricated from diamond are made from (100)‐oriented crystals. In this work, we demonstrate a methodology for the fabrication of optically active membranes from (111)‐oriented diamond. We use a liftoff technique to generate membranes, followed by chemical vapor deposition of diamond in the presence of silicon to generate homogenous silicon vacancy color centers with emission properties that are superior to those in (100)‐oriented diamond. We further use the diamond membranes to fabricate microring resonators with quality factors exceeding ~ 3000. Supported by finite‐difference time‐domain calculations, we discuss the advantages of (111)‐oriented structures as building blocks for quantum nanophotonic devices. Abstract : Despite tremendous advances in diamond photonics, so far, the majority of photonic devices fabricated from diamond are made from (100)‐oriented crystals. We fabricated large area (111) diamond membranes that exhibit bright SiV luminescence. These membranes are utilized to engineer diamond microring resonators with quality factors of ~ 3000. Our work launches a new approach for the fabrication of diamond devices with different crystallographic orientations.